Scaling and joint scaling test for quantitative traits of generation mean analysis insesame (Sesamum indicum L.): QUANTITATIVE TRAITS OF GENERATION MEAN ANALYSIS IN SESAME (SESAMUM INDICUM L.) - J JAWAHAR LAL; KULDEEP SINGH DANGI; SUDHEER KUMAR; J SURESH (Journal of Oilseeds Research, 2013)
Gene effects for important quantitative traits of five crosses of sesame (Sesamum indicum L.) were estimated by partitioning the means and variances of means of six basic generations from each cross into their genetic components to assess the gene action governing the inheritance of traits. The additive, dominance and digenic non-allelic gene interactions were observed to govern most of the yield traits. The non-additive gene effects were more pronounced than additive onesfor most ofthe traits. The A,B,C and D scalesshowed highly significant values for all the traits and crosses studied and departure from zero indicated the presence of epistasis. But, these tests verify only the presence of epistasis but do not provide the kind of gene action. This indicates the inadequacy of scaling and joint scaling test and presence of non allelic interactions. The next possibility is to include the effect of epistasis which can be estimated as additive x additive, additive x dominance and dominance x dominance gene effects in the inheritance of the characters.